(untitled) (SMC Journal Shadananda Multiple Campus, 2026)
The exponential growth of digital financial services and blockchain technologies has reshaped the structure of modern economies. This study investigates the relationship between digital transactions, blockchain technology, and the growth of the digital economy in Nepal using time-series data obtained from Nepal Rastra Bank and the World Bank. The analysis employs summary statistics, correlation analysis, and the Ordinary Least Squares method. Given heteroskedasticity and serial correlation, heteroskedasticity- and autocorrelation-consistent (HAC) standard errors based on the Newey–West estimator are used. Blockchain readiness shows a positive but marginally significant influence, suggesting economic impact remains limited. In contrast, internet usage shows a negative and significant relationship with the digital economy. Overall, the findings suggest that Nepal’s digital economy is primarily transaction-driven rather than innovation-driven. The study offers valuable insights for building financial infrastructure and improving institutional readiness to accelerate digital technologies for sustainable economic growth.